LANGUAGE ACQUISITION THROUGH SOCIAL MEDIA - Aarthi, M; Banu, M Dhilshath; Santhi, Ms S (International Journal of Psychosocial Rehabilitation, 2020)
Social Media refers to the means of interaction between people through communication. They share, create or exchange their ideas and information through networks. At present we live in the world of technology, competition and mainly social networking. Language practitioner and an educator custom social media as a tool for their development. Online English learning opportunities are interesting and dynamic. If we use a blog or forum site it will be interactive and more enjoyable. Apart from useful websites providing vocabulary the internet provides us with a means for communicating with students and teachers of English located in other parts of the world. Social Media is emerging in various forms to bring the people together in as communities. We cannot find a person without phone in the world. Basically, students find it difficult and inconvenient to deliver, share and present their views in front of others. Social Media helps the learners to reach the world outside the classroom through “Learning Technologies”. Nowadays, the young minds want to learn out of the class and around the world. Language learners are able to enhance their language skills due to the different avenues in which new social media have created.